“Síndrome de hubris y tipos de personalidad en profesionales de la salud. Riobamba, 2019” - Males Caiza, Katerin Elizabeth (2020)
The present investigation had the objective of analyzing the Hubris Syndrome and the types of personality in the health professionals who exercise direction and coordination of services (leadership) in health houses. The research was conducted in a population made up of 46 health professionals with undergraduate and postgraduate degrees. They are general practitioners and specialists (21); dentists and specialists (7); physiatrists (3); graduates in nursing (6); graduates in the clinical laboratory (2), clinical psychologists (3); nutritionist (1); and pharmaceutical biochemists (3). Type subjects are not probabilistic, because the required professionals were directly visited without obtaining a sample, intentional for the convenience of the researchers. The study approach was mixed (qualitative-quantitative), with a non-experimental and cross-sectional design, and it was also descriptive research. The instruments used were: the SEAPsI Personality Questionnaire and the Hubris Questionnaire. The results obtained are 28 health professionals (60.86%) present Hubris Syndrome; Regarding the type of personality, 29 health professionals (63%) are part of the anaclastic type; followed by the theatrical type in a lower percentage (15.20%). Dealing with the two variables, the presence of the syndrome in people with anarchistic personality was observed at a higher rate. Based on the prevention criteria, a workshop on psychological strategies, oriented to Hubris syndrome and character, was proposed in health professionals.